KURIKULUM PENDIDIKAN INDONESIA: ANTARA ADAB DAN INTELEKTUAL - Firmansyah, M. Feri (Pendidikan Agama Islam, 2019)
Education Indonesia is launching Character Education, which is education that aims to build the character of students to become civilized intellectuals. But it becomes an anomaly because in reality the students sometimes underestimate their teacher. This means that here Indonesia Education has not found the right formula for this concept. Different from the concept of Islamic Education, where Islamic Education is more comprehensive in shaping the character of students, namely through strengthening the spirit of their faith and adab. In other words, in the historical literature of the Islamic Education curriculum, there are two, namely the Curriculum of Faith and the Koran. After Faith and Al-Quran strong students then they recognize applied sciences, such as science, Social Sciences, and so forth.